The Role of Islamic Banking in Increasing the Awareness of Islamic Boarding School Students in Bangkalan Regency Regarding Islamic Financial Literacy - Riski Rahmawati; Alan Su’ud ma’adi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Sharia financial literacy is very important for santri because they are the young generation who will become economic leaders based on Islamic values, although there are still many challenges such as limited access to information. The main problem is the low understanding of Islamic financial institutions among the students. The research aims to analyze the role of Islamic banking in increasing students' awareness of Islamic financial literacy, focusing on knowledge, beliefs, and activities. The method used is a qualitative approach thru interviews, observation, and documentation at three Islamic boarding schools in Bangkalan Regency and Bangkalan Sharia Banking. The results show that students face limited access and an unsupportive curriculum, leading to low awareness of using sharia products. Additionally, there is a lack of socialization and education about Bank Syariah Indonesia KCP Bangkalan in Islamic boarding schools to support increased awareness among students.